Biodistribution of GB-10 (Na2 10B10H10) compound for boron neutron capture therapy (BNCT) in an experimental model of oral cancer in the hamster cheek pouch - Heber, Elisa Mercedes (2004)
Objective: We previously proposed the hamster cheek pouch model of oral cancer for BNCT studies. We herein present the biodistribution of a non-toxic boron compound, GB-10 (Na210B10H10), in this model to assess its potential for BNCT or BNCT enhanced Fast Neutron Therapy. Materials and methods: We evaluated the uptake and retention of GB-10 in tumour and precancerous tissue and in potentially dose-limiting, clinically relevant normal tissues. Results: Mean tumour boron concentration delivered by GB-10 (50mgB/kg) peaked to 77.7±28.0ppm at 20min post-administration and remained at therapeutically useful values of 31.9±21.4ppm at 3h. The clearance rate for normal tissues was faster than for tumour tissue. The consistently low brain and spinal cord values would preclude normal tissue toxicity. The uptake of GB-10 by precancerous tissue may be of potential use in the treatment of field cancerized areas. GB-10 was deposited homogeneously in different tumour areas, an asset when treating heterogenous tumours. The data suggests that the joint administration of BPA and GB-10 may improve the therapeutic efficacy of BNCT. Conclusions: GB-10 is a potential boron carrier for BNCT of head and neck tumours and for BNCT-FNT.